Adapting Da'wah and Empowerment: A Comparative Study of Islamic Women's Organizations' Transformation in West Java - Isnaeniah, Erni; Chodijah, Medina; Sujono, Hartin Rizky; Ihyana, Falya Alifa (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to analyze the dynamics of transformation that occurred in Islamic women's organizations in West Java, focusing on PW. Fatayat NU, PW. Nasyiatul Muhammadiyah, and PW. Persis young women for the 2020-2025 period. These organizations have a significant role in women's empowerment and public policy advocacy. Still, they face significant challenges stemming from social, political, and economic changes, including digitalization and changes in government policy. This research method uses a qualitative approach with case studies, collecting data through in-depth interviews with administrators and organization members and analyzing related documents. The research results show that Islamic women's organizations in West Java have successfully adapted to digital technology to expand the reach of da'wah and empowerment but still face internal challenges such as leadership regeneration and ideological differences. External challenges in socio-political dynamics and government policies force this organization to innovate and remain relevant. In conclusion, these organizations demonstrate strong transformational potential to contribute to more inclusive and sustainable social change despite the considerable challenges. This research implies the need to strengthen digital capacity, develop programs based on contemporary issues, and expand collaboration networks with various parties, including government and civil society.